Instrumentos administrativos para el fomento de la innovación tecnológica en el sector financiero peruano - Suárez Barcia, Lucía (Pontificia Universidad Católica del Perú, 2021)
This document strives to analyze the new approaches to regulatory supervision (innovation facilitators) that are being developed worldwide because of the fintech phenomenon, evaluating whether they would be beneficial for Perú, especially in relation to financial inclusion. For this reason, we have proceeded to a review of initiatives to promote fintech innovation worldwide, studying their characteristics. This analysis has a teleological nature of reviewing administrative supervision policies, grouping them into three large taxonomies: innovation centers, sandbox and others, such as innovation accelerators, studying in greater detail the sandboxes due to their relevance and potential impact. Specifically, the article explains the concept of sandbox, including the objectives for which they are designed, their main benefits and risks. Afterwards, the paper specifies the phases that these projects usually go through and their timelines. Two particular cases of sandbox are also described, the Mexican, which requires a «new model» license; and theIsraeli, focused on data. Subsequently, the potential benefits and challenges of applying this type of public policy in Peru are evaluated. Finally, a model is proposed for the country, aligned with the financial inclusion strategy, which allows the open participation of all types of entities, including those called fintech, for the greater benefit of society and the markets.

El presente documento trata de analizar los nuevos enfoques de supervisión regulatoria (facilitadores de innovación) que se están desarrollando a nivel mundial como consecuencia del fenómeno fintech, evaluando si pueden ser beneficiosos para Perú, especialmente en términos de inclusión financiera. Para ello, se ha procedido a la revisión de iniciativas de fomento de innovación fintech a nivel mundial, estudiando sus características. Este análisis tiene un carácter teleológico de revisión de políticas administrativas de supervisión, agrupándolas en tres grandes categorías: centros de innovación, sandbox y otros, como aceleradores de innovación, estudiando en mayor detalle los sandbox debido a su relevancia y potencial impacto. En concreto, se realiza una aproximación al concepto de sandbox, incluyendo los objetivos por los que se diseñan, sus principales beneficios y riesgos. A continuación, se especifican las fases que estos proyectos suelen atravesar y sus tiempos. También se describen dos casos particulares de sandbox: el mexicano, que requiere de licencia de «modelo novedoso»; y el israelí, centrado en los datos. Posteriormente, se evalúan los potenciales beneficios y retos de la aplicación de este tipo de políticas públicas en Perú. Finalmente, se propone un modelo para el país, alineado con la estrategia de inclusión financiera, que permita la participación abierta de todo tipo de entidades, incluidas las denominadas fintech, para un mayor beneficio de la sociedad y los mercados.
Administrative Instruments for the Promotion of Technological Innovation in the Peruvian Financial Sector
Keywords: innovation hubs; Innovation facilitators; Digitalization; Financial disruption; Fintech; Financial inclusion; Financial innovation; Financial markets; Regulatory policy; Regulatory sandbox; Centros de innovación; Digitalización; Disrupción financiera; Facilitadores de innovación; Fintech; Inclusión financiera; Innovación financiera; Mercados financieros; Política regulatoria; Sandbox regulatorio; https://purl.org/pe-repo/ocde/ford#5.05.01